PENGARUH GAYA MENGAJAR RESIPROKAL TERHADAP HASIL BELAJAR RENANG GAYA BEBAS SISWA SMP NEGERI 3 LUBUK PAKAM - Suharjo; Natalia Simanjuntak , Christin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the effect of the reciprocal teaching style on students’ learning outcomes in freestyle swimming at SMP Negeri 3 Lubuk Pakam. The problem underlying this research is the low mastery of freestyle swimming techniques among students, which is partly caused by the use of teacher-centered instructional methods that limit student participation and interaction. The purpose of this study was to examine whether the implementation of the reciprocal teaching style could significantly improve students’ freestyle swimming learning outcomes. This research employed an experimental method using a one-group pretest–posttest design. The population consisted of all eighth-grade students of SMP Negeri 3 Lubuk Pakam, with a sample of 32 students selected using probability sampling techniques. Data were collected through freestyle swimming skill tests administered before (pretest) and after (posttest) the implementation of the reciprocal teaching style. The collected data were analyzed using descriptive statistics and inferential analysis through a paired sample t-test. The results showed a significant improvement in students’ freestyle swimming learning outcomes after the application of the reciprocal teaching style. The findings indicate that the reciprocal teaching style effectively enhances students’ technical mastery, learning engagement, and overall performance in freestyle swimming. Therefore, this teaching style is recommended as an alternative instructional strategy in physical education, particularly in swimming lessons.